(untitled) (The Pakistan Development Review, 2010)
The present paper discuss the nature of structural changes in employment to understand jobless growth in Pakistan for the period spanning over 1967-2008. In our work (elsewhere)1 analysing Pakistan at sectoral level to find underlying factors generating jobless growth, we found that Jobless growth in manufacturing sector was anticipated. Industrial sector has a significant importance in any economy across the glob. Recent changes in the use of capital—based foreign technology has resulted in substitution of labour with non-labour inputs such as capital. Employment shifts between industrial sectors are often witnessed as indicators of Structural change in an economy. In this paper we are more interested in the nature of structural change that took place in Pakistan economy over 1967-2008. We set to analyse four commonly used measures of sectoral reallocation proposed by Lilien (1982), Groshen and Potter (2003), Rissman (1997), and Aaronson, Rissman and Sullivan (2004). Findings of our work are suggesting that the economy of Pakistan underwent structural change during periods of recession and recovery. However, it does appear that structural changes were more pronounced at the time of 1969 recession than that of 1991 recession. A plausible explanation for this result might be significant shifts in employment from agriculture towards services sectors. We conclude, based on the evidence from our study, that sectoral reallocation is one of the major causes of jobless growth in Pakistan.